La evocación de los perfumes en el Cantar de los Cantares. - Martínez, Adriana (Scripta Mediaevalia, 2026)
The Song of Songs is the last of the five poetic and wisdom books of the Old Testament, according to the version of the Seventy. Perhaps due to its originality, gave rise to varied interpretations that were based on both the literal reading and the allegorical reading. Specifically, his vocabulary of terms and expresssions from the plant world and his metaphors that recreate the senses, especially the olfactory sense, evoke a universe of aromas. Thus, we propose to trace in the poem the lexical and semantic networks of the plant language that crosses it and the ruptures or continuities that are reflected in the iconic plane.